The Contextual and Cultural Barriers to Equity and Full Inclusive Participation for People Labeled with Disabilities in Bangladesh - Dermot Foley (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} span.medium-bold {mso-style-name:medium-bold;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->Reviewing scholarship on the complex relationships between disability and poverty present in Bangladesh’s economy, micro-finance industry, poverty reduction strategy papers (PRSP) and laws, I explore how perspectives about disability exacerbated the problems and further disadvantaged people labeled with disabilities. Bangladesh has undergone economic, political and infrastructural change resulting in growth, yet the disparity in wealth between rich and poor is growing. The economic opportunity of an increasing non-farm labor force in Asian countries is a reality but who gets those opportunities now is limited to those without disabilities and, in some cases, without family members with disabilities. Attempts to assist those in poverty and labeled with a disability or having a family member labeled with a disability through micro-credit programs are often mired because lenders do not factor the greater cultural mechanisms of discrimination and, hence, they are not being constructively dealt with. Community based rehabilitation began in Bangladesh in the late 1980s; it was largely disability focused, served urban areas, and its theoretical orientation limited insight and opportunities to more effectively serve people labeled with disabilities. Finally, Bangladesh’s poverty reduction strategy papers and anti-discrimination laws have ignored issues of discrimination and stigma while providing limited participation from the community.